Marketing business processes in a multinational organization: A case study of an information system implementation - Valente, N.; Alturas, B. (Confronting security and privacy challenges in digital marketing, 2023)
Marketing information systems, scale, scope, and functionalities have grown due to the substantial rise of new technologies such as the internet, mobile devices, and social media. This chapter aims to analyse the impact of implementing a marketing information system to manage marketing business processes in a multinational organization. Interviews were carried out with organizations using the same marketing information system. The interview structure and its questions were based on the information system’s evaluation model, which is extensively used in this area of research. The results obtained were relevant not only from a benefits analysis perspective, but also from a system quality perspective, information quality and service quality matter.